Insecticidal activity and mechanism of action of phenylpropanoids isolated from Piper sarmentosum against storage insect pests and mosquito vectors / Arshia Hematpoor - Arshia, Hematpoor (2017)
The phytochemical and biological studies were carried out on medicinal and adible plant known as Piper sarmentosum L. (Piperaceae). Bioassay guided study of the active hexane and methanol extracts from aerial parts and roots of P. sarmentosum L. lead to isolation of four phenylpropanoids namely, asaricin 1, isoasarone 2, trans-asarone 3 and asaraldehyde 4. Their insecticidal activity and mechanism of action was investigated against storage pests (Sitophilus oryzae, Rhizopertha dominica and Plodia interpunctella) and mosquito vectors (Aedes albopictus, Aedes aegypti and Culex quinquefasciatus). Potent insecticidal activity against both species was produced by 1 and 2. Compounds 1 and 2 were highly toxic to S. oryzae with LC50 value of 4.7 and 5.6 respectively. R. dominica was slightly more resistance, P. interpunctella had highest resistant to 1 and 2 with LC50 value of ≤ 17.37 μg/ml and LC95 ≤ 37.7 μg/ml. asaricin 1 and isoasarone 2 exhibited high repellent activity against S. oryzae, R. dominica and P. interpunctella at 10 μg/ml. during the residual toxicity test it was observed that 1 and 2 had consistent activity within 30 days and their activity declined after that but compound 3 activity was consistent with 60 days of experiment. Likewise, 1 and 2 had potent larvicidal activity against Ae. albopictus, Ae. aegypti and Cx. quinquefasciatus. 1 and 2 similarly were highly potent against Ae. aegypti, Ae. albopictus and Cx. quinquefasciatus larvae with LC50 ≤ 8.9 μg/ml and LC95 ≤ 15.1 μg/ml . The ovicidal activity of 1, 2 and 3 were evaluated through egg hatching. 1 and 2 showed potent ovicidal activity. Ovicidal activity for both compounds was up to 90% at 25μg/ml. However repellent and adulticide activities of 1 and 2 against tested female mosquito was moderate. In all insecticidal tests compound 3 had moderate insecticidal activity and compound 4 did not have any insecticidal property. Biochemical investigation revealed that 1, 2 and 3 inhibit the acetylcholinesterase (AChE). Although 1 and 2 inhibition was stronger than 3 but correlation study showed that the toxicity of all three compounds was significantly related with their AChE inhibition activity. Further investigation for insect esterase activity showed that all insects had high GST activity and the level of GST was significantly higher in P. interpunchitela which had the highest resistance against 1, 2 and 3. The levels of non-specific esterases and oxidases activities were not significant between the tested insets. Further the docking studies were done to investigate the binding mode of interaction of 1, 2 and 3 with AChE and GST enzyme using Autodock/Vina. Between three active sites peripheral anionic site (PAS), catalytic and anionic in AChE, 1, 2 and 3 interact with more residues within 3 Å using a lower energy at anionic site. Compound 1 was interacted with TYR 370 pocket while 2 and 3 were more stable in THR 154, GLY 155, SER 156, TYR 162 at very low and stable energy level. Docking study on GST interactions with 1, 2 and 3 suggested that PRO11. GLU64 and TYR105 are more essential residues in GST for 1, 2 and 3 binding besides known active residues SER65 and ARG66. This can explain the high toxicity of 1 and 2. Biochemical and docking clearly showed the GST activity role in binding and detoxifying the 1, 2 and 3. Our result suggested that 1 and 2 were highly toxic to tested insects by inhibiting AChE enzyme and computation work supported and clarified the binding mode of interaction. Although compound 3 activity was not as significant as 1 and 2 but there is possibility of its usage in mixture as formulation in future study since it is more stable in the environment. On the other hand understanding the role of GST enzyme helped to develop knowledge on insects response to 1, 2 and 3. Further studies will warrant possible applications of 1, 2 and 3 as potential natural insecticide for the control of storage pests and mosquito vectors populations.